Oxidized phosphatidylserine mitigates LPS-triggered macrophage inflammatory status through modulation of JNK and NF-kB signaling cascades. - Maciel, Elisabete (2019)
Recent evidence suggests that phosphatidylserine (PS) and its oxidized species drive the clearance of apoptotic cells by macrophages with putative immune response modulation. However, it is not clear whether PS and oxidized PS differentially modulate at molecular level the functional responses of macrophages. Therefore, we proposed in this work to explore this question by evaluating the influence of PS oxidation products on the macrophages inflammatory status. Thus, we determined the effects of oxidized 1-palmitoyl-2-linoleoyl-phosphatidylserine (oxPLPS) and PLPS on RAW 264.7 macrophages production of the pro-inflammatory mediator nitric oxide (NO) and on the levels of the inducible NO synthase (Nos2) and Il1β mRNA. The ability of PLPS and oxPLPS to modulate the lipopolysaccharide (LPS)-triggered macrophage activation was also analysed. Finally, the effects of PLPS species over canonical inflammation-associated signaling pathways, such as nuclear factor (NF)-B and mitogen-activated protein kinases (MAPKs) were also disclosed. The results obtained showed that both PLPS and oxPLPS species are deprived of intrinsic pro-inflammatory activity. Exquisitely, only oxPS were found to significantly inhibit NO production and iNos and IL1 genes transcription induced by LPS. At a molecular level, these effects were partially due to attenuation of LPS-induced c-Jun-N-terminal kinase (JNK) phosphorylation and p65 NF-B nuclear translocation. Overall our data suggest that oxPLPS, but not native PLPS, mitigates pro-inflammatory signaling in macrophages, contributing to containment of inflammation during apoptotic cell engulfment.